2021
DOI: 10.1002/jcsm.12723
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic fat in liver and skeletal muscle is associated with shorter overall survival in patients with colorectal liver metastases

Abstract: Background Myosteatosis has been associated with shorter overall survival in cancer patients. The increase in ectopic fat might not be limited to skeletal muscle only and might also extend to other sites such as the liver, resulting in non‐alcoholic fatty liver disease (NAFLD). In this study, we assessed the relationship between myosteatosis and NAFLD and their association with overall survival in patients with colorectal liver metastases undergoing partial hepatectomy. Methods Patients were selected from a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…By contrary, survival was linked to body composition in 3 studies ( 43 , 46 , 47 ). In a retrospective Dutch trial including 196 patients (roughly 20% having sarcopenia), the authors found both reduced RFS and OS of 8.7 vs. 15.1 months (p=0.002) and 23.8 vs. 59.8 months (p=0.001) respectively in sarcopenic vs. non-sarcopenic patients.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…By contrary, survival was linked to body composition in 3 studies ( 43 , 46 , 47 ). In a retrospective Dutch trial including 196 patients (roughly 20% having sarcopenia), the authors found both reduced RFS and OS of 8.7 vs. 15.1 months (p=0.002) and 23.8 vs. 59.8 months (p=0.001) respectively in sarcopenic vs. non-sarcopenic patients.…”
Section: Resultsmentioning
confidence: 96%
“…Van Dijk et al., showed from a prospective cohort of 289 CRLM patients that NAFLD (p=0.037), myosteatosis (p=0.018), and sarcopenia (p=0.035) were independently associated with shorter OS while high visceral adipose tissue fat content was associated with longer OS (p=0.014). The authors concluded that ectopic fat content in liver as well as skeletal muscle is independently associated with shorter OS in patients undergoing liver resection for CRLM ( 47 ). In a previous study including 99 CRLM patients, the same authors advocated a correlation between host-phenotype of adverse body composition features (sarcopenia, low visceral adipose tissue) and systemic inflammation (C-reactive protein >5 mg/mL).…”
Section: Resultsmentioning
confidence: 99%
“…Body composition is highly variable among sex, age, race, and cancer types. 3,4,[14][15][16] For this reason, developed clinical cut-offs vary greatly among different patient cohorts and prognostic models of outcome (e.g. survival) are likely to fail during external validation.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, low skeletal muscle mass (i.e., sarcopenia), low adipose tissue mass, and decreased skeletal muscle radiodensity (i.e., myosteatosis) have been shown to be associated with shorter overall survival in various cancer types. [2][3][4] Body composition exhibits substantial heterogeneity among people due to natural variation in age, sex, race, and build. 5 These intrinsic inter-personal differences are unrelated to disease and may therefore obscure disease related body composition effects, necessitating large population-based data cohorts to adjust for them.…”
Section: Introductionmentioning
confidence: 99%
“…6 A previous study demonstrated that the presence of ectopic fat accumulation in the liver is independently associated with poorer overall survival (OS) in patients with colorectal liver metastasis (CRLM). 7 Prolonged storage of lipids in the liver can lead to liver dysfunction and inflammation, which play a crucial role in creating a metastatic-friendly environment that facilitates cancer seeding and colonization. 8 Moreover, CRLM patients with liver steatosis exhibit significantly shorter OS and hepatic recurrence-free survival.…”
Section: Introductionmentioning
confidence: 99%